An Evaluation of Teaching Practices, Challenges, and English Teachers’ Readiness in Implementing the Merdeka Curriculum in West Kalimantan Schools - Sahrawi; Maliqul Hafis (Universitas Islam Negeri Palopo, 2025)
This study aims to evaluate classroom learning practices, identify the challenges faced by teachers, and gather information regarding their readiness during the teaching and learning process in the implementation of the Merdeka Curriculum in junior high schools in West Kalimantan. This curriculum provides opportunities to enhance creativity and flexibility in learning. The study was conducted using a qualitative descriptive approach, in which participants were selected purposively, consisting of 20 English teachers—10 from urban schools and 10 from rural schools. Data were collected through interviews, observations, and document analysis. The data were analysed using Miles and Huberman’s principles, namely data reduction, data display, and conclusion drawing/verification. The findings show that most teachers have implemented the Merdeka Curriculum, with 80% implementation in urban schools and 40% in rural schools. Teachers encountered several challenges, including limited supporting facilities, inadequate access to technology, and uneven human resource capacity. The results also indicate that most teachers feel ready to implement the curriculum, although their levels of readiness are not uniform. Nevertheless, evaluations from various stakeholders play a significant role in enhancing the successful implementation of this curriculum.